A Focus on Action Speed Training - Feldmann, K.
Recent analyses of major international events (ECh, WCh and Olympics) have been highlighting the fact that European top teams have further developed their execution of the game. This, however, has not involved highly obvious changes such as new tactical concepts and formations but, more importantly, minor steps including · more fast breaks in the game and efficient exploitation of opportunities arising from such breaks, · active, variable defence action with small, fast steps, frequently culminating in recovery of the ball as well as · a larger number of attacks in each game with shorter preparation times and faster execution. Underlying all these tendencies in game development is higher playing speed and faster action as exhibited by teams from Africa and Asia. This style of playing has more recently also been encouraged by the IHF through its rule revisions (e.g. fast throw-off and early warning for passive playing). Training activities taking into account these new developments will therefore include the following aspects in the future: · quicker perception and information processing, also on the part of those playing without the ball, · greater demands made on legwork to support flexible defence action, · speed-driven application of attack techniques and · improvements in switching from defence to attack and from attack to defence.